Sistem Sinkarkes dalam Penerbitan SSCEC dan P3K pada Kapal oleh PT. Surya Samudera Indah Batam - Sofia Lazuba Purba; Syarifur Ridho; Taruna Ginting (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research aims to comprehensively describe and understand the utilization of the SINKARKES system (Ship and Health Information System) in the issuance of the Ship Sanitation Control Exemption Certificate (SSCEC) and the First Aid for Accidents (P3K) Certificate for vessels managed by PT. Surya Samudera Indah Batam. Compliance with ship sanitation and health standards is a mandatory prerequisite for preventing disease spread and ensuring occupational safety in accordance with prevailing regulations. The research methodology employed is field research (field research) to observe direct operational procedures in the field, supplemented by literature review (library research) to strengthen the theoretical and regulatory foundations of the Ministry of Health. The findings indicate that the process of issuing the certificates through SINKARKES begins with agent login access to the official application (sinakarkes.kemkes.go.id) using a registered company account. Subsequently, the agent submits an application for SSCEC and P3K issuance, followed by the completion of data and the uploading of mandatory supporting documents. These documents include the Maritime Health Declaration (MDH), previous SSCC/SSCEC certificates, the P3K certificate, crew list, voyage memo, and the list of last ports of call. Once the documents are verified, the Special Health Quarantine Officer (KarKessus) proceeds to conduct a physical survey onboard the vessel. The main obstacle encountered is poor internet network connectivity in the port area, which often leads to data input failures and double entry errors during certificate printing.